Tooth Surface Temperature Rise Analysis of Spiral Bevel Gear During Dry Running - Yan Hongzhi; Zhou Tengfei; Huang Guobing; Xiao Meng; Hu Zhian (Jixie chuandong)
According to the meshing and forming principle,the tooth surface equation of spiral bevel gear is established. The spiral bevel gear loaded contact analysis is carried out by using finite element method,and the contact positive pressure,relative sliding speed and friction coefficient of the tooth surface 10 meshing points are obtained. By applying heat transfer theory and based on the analysis of the friction heat and the heat conduction parameters,the finite element model of the unsteady temperature field of spiral bevel gear is established,and the simulation analysis of the tooth surface temperature field distribution and its variation with time during the dry running is carried out. The results show that during the initial stage of the dry running of the spiral bevel gear,with the increasing of the meshing period,the tooth surface temperature rising rapidly,and then rising slowly,the temperature rising is accompanied by fluctuations which correspond to the meshing cycle. The increasing of the meshing speed prolongs the time that temperature rise rapidly,and it leads more significant temperature rising at the same time.